Facial feature extraction for facial animation - Madrinan, Michael T.; Palma, Alexander L.; Rosos, Joan Maris D.; Uy, Jonel N. (Quezon City College of Engineering, University of the Philippines Diliman, 2000)
With the objective of developing a real time facial animation system, this paper tries to apply the Snakes Algorithm. Initially treating the sequence of images generated by the video individually, the LVQ algorithm is used to generate reliable code book vectors for skin segmentation. After which the image is stored in grey scale format. In anticipation for the necessity of edge detection, a method called Sobel Edge En- hancement is employed. The Sobel edge enhancement particularly makes use of a convolution mask where the intensity of a certain pixel is calculated based on the values of its surrounding pixels.
Following the edge enhancement is the Edge Sign Map Generation which displays more obvious facial contours. The algorithm, searches for light to dark and dark to light areas. These resulting regions are then used as the basis for indicating the boundaries of the facial feature regions. Having the facial feature regions of the eyes, eyebrows, and mouth, the Snake is applied to each of them; iterated until it converges to the edges of the given facial region. The main purpose is for the extraction of the feature points.

Ideally, these extracted feature points will serve as the control points for a given or generated facial mask (3D or 2D) that will be used for animation. However, due to time and opportunity constraint, the extracted control points are just displayed on another form for each of the processed images.
Thesis (Bachelor of Science in Computer Science)--University of the Philippines Diliman
Keywords: Facial expression -- Computer simulation; Computer animation; Three-dimensional imaging